Global burden of lung cancer attributable to metabolic and dietary risk factors: an overview of 3 decades and forecasted trends to 2036 - Xiang, Yuying; Chen, Yun; Lan, Lingyan; Chen, Shuling; Shu, Qijin (Frontiers in Nutrition, 2025)
BackgroundLung cancer (LC) is the leading cause of cancer-related burden worldwide. Unhealthy dietary patterns and related metabolic diseases, such as diabetes mellitus (DM), represent critical global public health challenges. Nevertheless, the global burden of LC attributable to metabolic and dietary factors remains uncertain.MethodsThis study aims to analyze global burden of LC attributable to metabolic and dietary risk factors, based on the Global Burden of Disease (GBD) 2021, from 1990 to 2021. Additionally, the autoregressive integrated moving average (ARIMA) model was utilized to forecast the disease burden of LC for the upcoming 15-year period.ResultsHigh fasting plasma glucose (HFPG) and Diet low in fruits (DLF) are identified as the sole metabolic and dietary risk factors for LC, respectively, according to GBD 2021. The study findings indicate that a marked increase in the LC burden caused by HFPG, whereas the age-standardized rates (ASRs) of mortality and disability-adjusted life-years (DALYs) attributable to DLF for LC represent a general decline. At the social population index (SDI) regional level, the burden of LC attributable to DLF represents the most rapid increase in low-middle SDI regions, and while, the burden of LC attributable to DLF exhibits the most rapid decline in high-middle SDI regions. Moreover, LC burden attributable to HFPG and DLF in mortality and DALYs is higher among males than females, with sex difference being more pronounced in the elderly.ConclusionFrom 1990 to 2021, the burden of LC attributed to HFPG has increased owing to the escalating exposure levels of DM, whereas the burden resulting from DLF has declined. The burden of LC attributable to HFPG and DLF exhibits distinct spatiotemporal patterns and similar gender-age patterns.